« Une peinture effrayante et splendide », la réception de Greco en France (1843-1956) - Charlotte Chastel-Rousseau (E-Spania)
The historiographical perspective highlights the variation in judgments that have been made on Greco's production: various sources serve in support of the demonstration to account for how painters, authors and art historians have judged the work of Greco through the centuries. Lifting the veil on parts of shadows and mystification, this study establishes a diachronic typology of the reception of Greco in France not only from the literature written about the artist but also by analyzing the reception of the works of the Cretan. exhibited in France.